Teaching at a Distance with the Merging Technologies: An Instructional Systems Approach - Michael T. Harrington (Journal of Applied Communications, 1998)
A review of Teaching at a Distance with the Merging Technologies: An Instructional Systems Approach, by Thomas E. Cyrs with Eugenia D. Conway.